Retrograde-Antegrade Snaring With Electrosurgery and Removal of a Ruptured Papillary Muscle. (June 2020) - Bode, Michael F.; Mintz, Ari J.; Shaikh, Nadia; Alhajri, Fahad; Baron, Suzanne J.; Gadey, Gautam; Labib, Sherif B.; Piemonte, Thomas C.
Abstract : Supplemental Digital Content is available in the text.